Geochemical correlation of igneous events in the Project Esperanza, district Bolognesi, department Ancash - Quispe Arquíñego, Marleny (2013)
Few regional studies by a relationship type magma and their metal occurrences. During the producing rock formation magmas (“fertile”) and non-producing (“sterile”) are developed. It is therefore important to determine which controlled variations in geochemical signatures or footprints of these rocks, interpret magmatic events in space-time to thereby focus mineralogy in the study area The Esperanza Project on the basis of geochemical characterization of igneous events represented by monzodioritic stock, andesitic dykes and lavas, dacitic dikes and stock and concludes that they are of volcanic arc tectonic environment in subduction zones. The monzodiorite is the most ancient, the one with higher degree of oxidation and wet from magmas and hydrothermal alteration that more presents, so we assumed that this intrusive is responsible for the generation and release of fluids related to mineralization the study area.